A GENRE-BASED TEXTUAL ANALYSIS OF EXPERT ONLINE REVIEWS OF ELECTRIC GUITAR FUZZ PEDALS - Che Moya (Indonesian Journal of Integrated English Language Teaching, 2017)
This study uses genre analysis to analyze contemporary online text.  Through an analysis of the linguistic features of text from a highly specialized discourse community, perceived expert online reviews of electric guitar fuzz pedals, findings from this study provide insight into the relevance of online reviews. Although there is a layman quality to the actual production of the textual online reviews, genre analysis reveals hybridized genres, authorial power within occluded genre chains, subconscious marketing techniques, and manipulation of perceived expert online reviews. Findings from this study indicate that online reviews have complex occluded genre chains, which are not readily obvious when the reviews are read only for entertainment purposes.  This research has real world applications as relationships between textual generic qualities of online reviews and consumer spending habits are now easily acquired from online data-mining techniques to assist in targeting online consumers’ habits and to increase sales. Online reviews are now what consumers use to assist in shopping. Control of reviews translates to control of consumers’ shopping habits.